2016
DOI: 10.1093/rpd/ncw246
|View full text |Cite
|
Sign up to set email alerts
|

PATIENT SIZE BASED GUIDING EQUATIONS FOR AUTOMATIC mAs AND kVp SELECTIONS IN GENERAL MEDICAL X-RAY PROJECTION RADIOGRAPHY

Abstract: A patient size based guiding equation for the automatic selections of mAs and peak voltage kVp in general medical X-ray projection radiography was derived from the first principles of dose and image quality optimization. Under various specific conditions of constant patient size d, kVp or mAs, this equation leads to various longstanding 'rules of thumbs' currently being employed in clinical practice. For automatic mAs control, this work suggests that the current level of dose to patient in X-ray radiography sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…An ideal value of n=3.33 was suggested for the 15% 'rule of thumb' (Ching et al 2014), i.e. for a 15% increase of kVp, half the mAs, in our earlier study (Zheng 2016a). It was also suggested that the dose at the body centre should be taken as dose reference rather than detector absorbed dose, or dose at the exit surface (Zheng 2016a).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…An ideal value of n=3.33 was suggested for the 15% 'rule of thumb' (Ching et al 2014), i.e. for a 15% increase of kVp, half the mAs, in our earlier study (Zheng 2016a). It was also suggested that the dose at the body centre should be taken as dose reference rather than detector absorbed dose, or dose at the exit surface (Zheng 2016a).…”
Section: Discussionmentioning
confidence: 84%
“…In our recent works (Zheng 2016a(Zheng , 2016b, the averaged powers of x-ray tube dose output were employed in the derivations of governing equations for automatic selection of optimal scan parameters, mAs and kVp, in clinical x-ray imaging including CT (Zheng 2016b) and computed radiography or direct digital radiography (Zheng 2016a). The x-ray tube dose power n was assumed to be an imaging system dependent-constant together with the size specific dose correction factor constant γ in these mathematical derivations (Zheng 2016a(Zheng , 2016b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faktor eksposi dapat dipilih dengan menyesuaikan tiap-tiap ukuran bagian tubuh dan kondisi patologis tertentu sehingga memperoleh kualitas citra sebaik mungkin (Long et al, 2019). Pada pasien yang memiliki pelvis tebal (lebih dari 20 cm) dianjurkan untuk menambah kondisi faktor eksposi dengan tujuan agar menghasilkan citra yang optimal sehingga dapat digunakan radiolog dalam melakukan diagnosa (Zheng, 2017;Metaxas et al, 2019).…”
Section: Pendahuluanunclassified
“…Dalam penggunaan CR, perlu diperhatikan beberapa faktor yang mempengaruhi yang salah satunya penggunaan filter pesawat sinar-X berdasarkan penelitian oleh bahwa dengan peningkatan nilai filter diikuti dengan kenaikan nilai EI (Ekpo et al, 2014). Penggunaan nilai mAs dapat disesuaikan dengan ukuran tubuh pasien dimana apabila terjadi peningkatan 1 cm tubuh pasien maka dikompensasi dengan penambahan 15% nilai mAs (Zheng, 2017), disarankan bahwa pada pasien dengan ketebalan tubuh standar sebaiknya menggunakan teknik kV standar dengan dengan menyeimbangkan dosis radiasi yang diterima dan kualitas citra yang dihasilkan, kemudian untuk pasien dengan ketebalan tubuh lebih besar, maka dapat menggunakan teknik kV tinggi dengan tetap mengutamakan upaya optimisasi agar tercapai konsep ALARA (Metaxas et al, 2019). Selain itu, pengalaman klinisi radiografer menjadi penentuan pemilihan faktor eksposi dan analisa kualitas citra yang dihasilkan, dimana radiografer dapat mengupayakan optimasi citra dengan pertimbangan pemilihan faktor eksposi untuk EI yang optimal dari ukuran tubuh, peralatan CR dan pesawat sinar-X yang digunakan.…”
Section: Pembahasanunclassified